An empirical study on entrepreneurial traits and their impact on enterprise success - Sthitaprajnya Pattanayak; Munindra Kakati (Vilakshan (XIMB Journal of Management))
Purpose – Enterprise success is driven by enterprise actions, which, in turn, is influenced by entrepreneurial behaviours. Behaviours are guided by traits. Hence, it is highly likely that personality traits of entrepreneur are critical to enterprise success. This paper aims at finding the relationship between entrepreneurial traits and enterprise success, identify underlying construct and examine how successful and unsuccessful entrepreneurs differ across traits. It also attempts enterprise profiling based on these traits and test predictive validity of entrepreneurial traits on enterprise success. Design/methodology/approach – In this study, 396 micro, small and medium enterprises comprising both successful and unsuccessful ones are studied together across 11 personality traits. Data was analysed using various statistical techniques like co-relation, t-test, factor analysis, cluster analysis and regression to test hypothesis and arrive at given findings. Findings – This study finds there is strong positive co-relations between traits and enterprise success. It establishes that successful and unsuccessful enterprises display distinct traits and significantly differ from each other. Entrepreneurial traits affect enterprise success, and the former has significant predictive value on the later (R-squared = 0.866). Practical implications – The findings have implications to entrepreneurs in relation to enriching the existing traits and inculcating new ones. Financial institutions like banks can peruse the findings and include traits and behavioural aspects in borrower selection, credit appraisal, evaluation and credit decisioning, to make it more holistic. It also generates scope for further academic research. Originality/value – This study contributes to existing literature and validates existing findings. It also finds that traits are contagious in nature, together of which can be grouped to build an entrepreneurs’ traits index which exerts strong influence on enterprise success.